"You Can't Hide Your Lyin' Eyes": Investigating the Relationship Between Associative Learning, Cue Awareness, and Decision Performance in Detecting Lies. (June 2020) - Morrison, Ben W.; Johnston, David; Naylor, Mathew; Morrison, Natalie M. V.; Forrest, Daniel
Although skilled cue utilization is presumed to result primarily from domain-specific experience, individual differences in learning are theorized to play a significant role. Using a single-group correlational design, this study tested whether individuals' domain-general associative learning capacity was related to performance in a complex real-world decision task presumed to rely heavily on cues: lie detection. A total of 21 participants completed an associative learning task in the form of a Space Invaders-like game. In the game, those who learn the cues are able to respond faster to the appearance of an enemy ship. Participants were also surveyed on their awareness of cues in the game. This was followed by a lie detection task. It was hypothesized that greater associative learning would be associated with greater awareness of cues in the learning task, and subsequently, superior accuracy in the lie detection task. Participants' associative learning was correlated with their cue awareness ( r pb = .782, p < .001). Further, learning was associated with better performance in the lie detection task ( r = .544, p = .011); however, accuracy was found to be unrelated to the types of cues reportedly used during detection. These findings have implications for our understanding of cue acquisition and expertise development.